2019
DOI: 10.1038/s41372-019-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and Bayley-III correlates of early hand function in extremely preterm children

Abstract: Objective(s)-Investigate associations between 18 and 22-month corrected age hand function, adverse findings on serial cranial ultrasound (CUS) and near-term brain MRI (ntMRI), and Bayley-III scores in extremely preterm (EPT) toddlers. Study design-Cohort analysis of Neonatal Research Network SUPPORT NEURO data. Associations between brain abnormalities, hand function, and Bayley-III scores were examined using chi-square and generalized linear mixed effect model analyses. Results-A total of 433 children were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Early Hand Function.-Pincer and grasp capacity, exaggerated hand preference, and ability to perform bimanual functions were assessed in detail at 18-22 months of corrected age using the 'hand function', 'upper limb function', and 'hand preference' subsections of the standardized NRN neuromotor examination (1). Clinicians trained and certified annually in this assessment perform this examination.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Early Hand Function.-Pincer and grasp capacity, exaggerated hand preference, and ability to perform bimanual functions were assessed in detail at 18-22 months of corrected age using the 'hand function', 'upper limb function', and 'hand preference' subsections of the standardized NRN neuromotor examination (1). Clinicians trained and certified annually in this assessment perform this examination.…”
Section: Methodsmentioning
confidence: 99%
“…NRN examiners assessing hand function were masked to hospital morbidities. The Motor scale of the Bayley Scales of Infant-Toddler Development, 3 rd Edition was not part of the 18-22 month NRN assessment until after 2010, and was not available for the children included in this study (1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While MRI has not yet emerged as a solitary tool, its role as contributing important data cannot be overlooked. It is for this reason that there is a consideration for TEA MRI to be integrated into a more extensive assessment, including physical examination findings, clinical risk factors (e.g., neonatal history of bronchopulmonary dysplasia and postnatal steroids) [ 151 , 152 ], standardized neurological and motor assessments (e.g., General Movement Assessment (GMA) [ 153 , 154 , 155 ], Hammersmith Infant Neurological Examination (HINE)) [ 155 , 156 , 157 , 158 ] for early identification of motor challenges, mainly CP [ 159 , 160 , 161 , 162 , 163 ]. In a retrospective case–control study of 441Italian high-risk infants, Morgan et al, 2019 found that the combined predictive power of the three-month HINE, GMA, and neuroimaging (MRI and/or cranial US) post-term gave sensitivity and specificity values of 97.86% and 99.22% (PPV 98.56%, NPV 98.84%) for detecting CP [ 164 ].…”
Section: Moving From Research To Clinical Practicementioning
confidence: 99%